2012
DOI: 10.1080/13504630.2012.709002
|View full text |Cite
|
Sign up to set email alerts
|

Dignity, happiness and being able to live a ‘normal life’ in the UK – an examination of post-accession Polish migrants' transnational autobiographical fields

Abstract: This article examines data from a qualitative study of post-accession Polish migrants living in the UK. We examine themes from our interviews such as 'dignity', 'normality', 'happiness' and the 'affordability' and 'ease' of life in the UK (compared to Poland). We focus on the autobiographical or intra-personal discursive practices that define what Habib calls migrants' continuing relationship with their 'homeland'. We draw on Emirbayer and Mische's analysis of the relationship between 'agency' and what they ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 19 publications
3
50
0
1
Order By: Relevance
“…This image of Eastern European migrants only being in the West on a temporary basis has somewhat hampered the research on the return migration of these migrants, because – what is there to study if it is given that they do not want to stay? However, some recent research (see Krings et al, ; McGhee et al, ) has found that the nature of East‐West migration might not be as temporary as predicted. At least before Brexit, many Poles in the UK were planning to stay, referring to a more dignified life in the UK.…”
Section: After Eu Accession In 2004 – Highly Mobile Eastern Europeansmentioning
confidence: 88%
“…This image of Eastern European migrants only being in the West on a temporary basis has somewhat hampered the research on the return migration of these migrants, because – what is there to study if it is given that they do not want to stay? However, some recent research (see Krings et al, ; McGhee et al, ) has found that the nature of East‐West migration might not be as temporary as predicted. At least before Brexit, many Poles in the UK were planning to stay, referring to a more dignified life in the UK.…”
Section: After Eu Accession In 2004 – Highly Mobile Eastern Europeansmentioning
confidence: 88%
“…Secondly, we wished to de-emphasise 'temporariness' and 'fluidity'; Polish migrants, qua EU citizens, may remain undetermined about plans for the future without necessarily becoming 'temporary' residents, given that they automatically acquire permanent resident status after five years of exercising free movement rights. Also, 'indeterminacy' can arguably be construed as supportive of the oft-described quest for a 'normal life' among those who have been resident for longer and have begun establishing families, as evading the necessity to formulate clear return or settlement plans can enhance the sense of 'normalcy' by essentially normalising transnational forms of belonging and activity across the lifecourse (Galasińska and Kozłowska 2009;Lopez Rodriguez 2010;McGhee, Heath, and Trevena 2012;Morokvasic 2004). …”
Section: Migration Strategies and The Habitus Of 'Indeterminacy'mentioning
confidence: 99%
“…Taking into consideration the above, our aim here is therefore to find out what factors contribute towards determining the migration and 'civic integration' strategies of Polish migrants in the UK (1) over a normatively relevant medium-term time frame and (2) under the conditions created by the UK's vote to leave the EU. Our approach, therefore, acknowledges that long-term plans are changeable and hard to determine (Burrell 2010;Parutis 2014), and also that 'indeterminacy' and 'civic integration' can both be manifestations of different forms of transnational living (McGhee, Heath, and Trevena 2012;Morokvasic 2004;Ryan 2011;White and Ryan 2008).…”
Section: A Rights-based Approach To Migration Strategiesmentioning
confidence: 99%
“…Many find themselves on a quest to establish more grounded lives, which is indicative of the significance of qualitative measures of economic factors. Here, the relevant economic factors are not restricted simply to having a job -or an income -but rather extend to the ability to lead what some interviewees called a 'normal life' (see also McGhee, Sue, and Trevena 2012), and what others described as a decent life, or living with dignity. This notion encompasses a decent 'working life' (Galasińska and Kozłowska 2009).…”
Section: Where Does Your Future Lie?mentioning
confidence: 99%